Fighting arsenic at the grassroots: experience of the community awareness initiative of BRAC in Bangladesh - Hadi, Abdullahel (BRAC Research and Evaluation Division (RED), 2019)
The study evaluates the arsentc mitigation project of BRAC in ra1smg the awareness of arsenic poisoning in the rural communities in Bangladesh. Data came from the selected villages in the southwestern Bangladesh where BRAC had arsenic mitigation project. Comparison villages were also selected from the same region. A total of 1,240 randomly selected adult persons were interviewed in May 2000. Findings reveal that the mitigation project played a significant positive role in raising awareness of the safe water options, signs of arsenicosis, mode of transmission and the type of treatment. Testing tube-well water for arsenic created curiosity, innovations and interest in the community. Similarly, water treatment plant became a symbol of arsenic campaign that created the context for promoting awareness. The study concludes that the behavioural change aspects of the arsenic mitigation project have the potential to significantly improve the level of understanding about arsenic contamination in the traditional communities.